Building energy simulation a workbook using DesignBuilder - Garg, Vishal; Mathur, Jyotirmay 1969-; Bhatia, Aviruch (CRC Press, 2020)
The 2nd edition of the Building Energy Simulation book include study of various components and systems of a building and their effect on energy consumption, with the help of an energy simulation tool, DesignBuilderTM, a commercial front-end for EnergyPlus simulation engine, supported by numerous examples and exercises. Following a "learning by doing" methodology, it explains simulation input parameters, along with how to do analysis of the simulation output explaining the basics of building physics and energy simulation. Divided into three sections, the first section provides fundamentals of energy simulation followed by advanced topics in energy simulation and simulation for compliance of building codes and detailed case studies for whole building energy simulation. Aimed at students and researchers in building energy courses, energy simulation professionals, architects, this book:Focuses on learning building energy simulation while being interactive through examples and exercises.Explains the building physics and the science behind energy performance of buildings.Encourages integrated design approach by explaining the interactions between various building systems and their effect on energy performance of building.Discuses "how to" model for building energy code compliance including three projects to practice whole building simulation".Provides hands-on training of building energy simulation tools: DesignBuilder and EnergyPlus.
Keywords: Energiebewusstes Bauen; Simulation; Energieverbrauch; Gebäude; Building Energy Consumption; Building Physics; Energy Codes; Green building certification; Performance Evaluation of Buildings